Only Acyl Carrier Protein 1 (AcpP1) Functions in Pseudomonas aeruginosa Fatty Acid Synthesis - Ma, Jin-Cheng; Wu, Yun-Qi; Cao, Dan; Zhang, Wen-Bin; Wang, Hai-Hong (Frontiers in Microbiology, 2017)
The genome of Pseudomonas aeruginosa contains three open reading frames, PA2966, PA1869 and PA3334, which encode putative acyl carrier proteins, AcpP1, AcpP2 and AcpP3, respectively. In this study, we found that, although these apo-ACPs were successfully phosphopantetheinylated by P. aeruginosa phosphopantetheinyl transferase (PcpS) and all holo-forms of these proteins could be acylated by Vibrio harveyi acyl-ACP synthetase (AasS), only AcpP1 could be used as a substrate for the synthesis of fatty acids, catalyzed by P. aeruginosa cell free extracts in vitro, and only acpP1 gene could restore growth in the Escherichia coli acpP mutant strain CY1877. And P. aeruginosa acpP1 could not be deleted, while disruption of acpP2 or acpP3 in the P. aeruginosa genome allowed mutant strains to grow as well as the wild type strain. These findings confirmed that only P. aeruginosa AcpP1 functions in fatty acid biosynthesis, and that acpP2 and acpP3 do not play roles in the fatty acid synthetic pathway. Moreover, disruption of acpP2 and acpP3 did not affect the ability of P. aeruginosa to produce N-acylhomoserine lactones (AHL), but replacement of P. aeruginosa acpP1 with E. coli acpP caused P. aeruginosa to reduce the production of AHL molecules, which indicated that neither P. aeruginosa AcpP2 nor AcpP3 can act as a substrate for synthesis of AHL molecules in vivo. Furthermore, replacement of acpP1 with E. coli acpP reduced the ability of P. aeruginosa to produce some exo-products and abolished swarming motility in P. aeruginosa.